Handphone Mempengaruhi Terhadap Perilaku Remaja Usia SLTP (13-15 Tahun) Di Dusun Tegalpare Kecamatan Muncar Kabupaten Banyuwangi - Abdul Aziz (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2016)
Advances in communication and information technology such as mobile phones not only hit the people who live in urban areas but can be enjoyed by people in remote villages. People who once so thick with their culture little by little more lost. This research is focused on "Mobile Affect Against Behavior of Juvenile Junior High School (13-15 Years) in Tegalpare Village Wringinputih Village Muncar Sub-district of Banyuwangi Regency". This research uses the descriptive method with case study technique. Research using interview and observation technique of participant. After the researcher conducted observation and interview at adolescent in Tegalpare sub-village, Muncar sub-district resulted that influence of behavior pattern of Tegalpare Dusun due to the use of mobile phone has very big negative effect in education, social and religious life. Because they become lazy to socialize with friends and the environment, lazy to learn even lazy worship which is their obligation as Muslims. Thus handphone gives influence to the behavior of junior high school age (13-15 years) in Tegalpare Village Wringinputih Village Muncar District Banyuwangi District